2008
DOI: 10.1016/j.watres.2008.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the partitioning behavior of Giardia and Cryptosporidium with that of indicator organisms in stormwater runoff

Abstract: Microbial association with particles can significantly affect the fate and transport characteristics of microbes in aquatic systems as particle-associated organisms will be less mobile in the environment than their free phase (i.e. unattached) counterparts. As such, similarities or dissimilarities in the partitioning behavior of indicator organisms and pathogens may have an impact on the suitability of a particular indicator to act as a surrogate for a pathogen. This research analyzed the partitioning behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 32 publications
1
43
2
2
Order By: Relevance
“…The importance of clostridia as a removal indicator for both Cryptosporidium and Giardia in drinking water treatment using rapid sand filtration [11] and in sewage treatment using activated sludge [12] has also been reported. Furthermore, since C. perfringens is resistant to chlorination and can be used as a surrogate indicator of water treatment effectiveness for protozoa and other chorine-resistant pathogens [4,11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of clostridia as a removal indicator for both Cryptosporidium and Giardia in drinking water treatment using rapid sand filtration [11] and in sewage treatment using activated sludge [12] has also been reported. Furthermore, since C. perfringens is resistant to chlorination and can be used as a surrogate indicator of water treatment effectiveness for protozoa and other chorine-resistant pathogens [4,11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of stormwater loadings of Cryptosporidium and Giardia in the New York Kenisco Reservoir directly compared the partitioning behavior of these protozoans with the behavior of several indicator organisms (Cizek et al 2008). Observations suggested that 15-30% of fecal indicator bacteria and over 50% of (oo)cysts are associated with settleable particles.…”
Section: Introductionmentioning
confidence: 99%
“…; Fries et al 2006;Krometis et al 2007;Cizek et al 2008). Use of a single separation technique allows for a direct comparison of the partitioning behavior of indicators and Salmonella spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither E. coli nor C. perfringens, suggested as suitable indicators for Giardia and Cryptosporidium [25,26], were detected in the 100-mL samples. This well was known to be located in the middle of a rural village and close to a road.…”
Section: Discussionmentioning
confidence: 83%